Is American power declining? - Gabr, Mohamed (AUC Knowledge Fountain, 2011)
According to popular understanding, America rose to the forefront of the international system when the fall of the Berlin Wall (1989) marked the end of the Cold War era singling America out as the world's only superpower. However, America's share of the global economy actually reached its peak during the 1950s in the midst of the Cold War and shortly following the end of the Second World War. Ever since then, it is a matter of fact that America's share of the global economy has been gradually declining, as confirmed by a multitude of indicators. In the 1970s, in the wake of the abandonment of the Gold Standard (1971), the oil crisis and ensuing stagflation that followed in the American economy (1973), and America's failure in the Vietnam War (1975), numerous scholars argued that America has entered a phase of hegemonic decline. Throughout the 1980s and thereafter, those views on American decline have been shared by various scholars from different backgrounds, while other scholars refuted this assertion claiming, albeit for different reasons, that American power is actually stable if not increasing.